Evaluating the Effectiveness of South Africa’s Prevention of Domestic Violence Act in Reducing Gender-Based Violence in Cape Town - Ayanda Zulu (Studies in Law and Justice, 2024)
This study evaluates the effectiveness of South Africa’s Prevention of Domestic Violence Act (PDVA) in reducing gender-based violence in Cape Town. The research examines the key provisions and objectives of the PDVA, its impact on reported cases of domestic violence, and the roles of law enforcement and community organizations in its implementation. Despite increased reporting and awareness following the Act’s introduction, significant challenges remain, including resource limitations, training gaps, and societal attitudes that hinder effective enforcement. The study identifies gaps in public awareness and societal support as critical barriers to the PDVA’s success, suggesting that legal reform alone is insufficient without broader social and institutional changes. Recommendations are made to enhance law enforcement capacity, improve community support mechanisms, and strengthen public education initiatives to achieve a more comprehensive and effective response to domestic violence.